2011
DOI: 10.1038/hr.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic gene expression in ω-3 PUFA-deficient male rats before, and following, development of hypertension

Abstract: Dietary deficiency of ω-3 fatty acids (ω-3 DEF) produces hypertension in later life. This study examined the effect of ω-3 DEF on blood pressure and hypothalamic gene expression in young rats, before the development of hypertension, and in older rats following the onset of hypertension. Animals were fed experimental diets that were deficient in ω-3 fatty acids, sufficient in short-chain ω-3 fatty acids or sufficient in short- and long-chain ω-3 fatty acids, from the prenatal period until 10 or 36 weeks-of-age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…In light of this evidence, it is interesting that Begg et al 22 reported in this issue that the expression of angiotensin-II 1A receptors and dopamine D3 receptors was significantly increased in the hypothalamic tissue of o-3-deficient animals at age 10 weeks, and the a2a and b1 adrenergic receptor expression was significantly reduced at 36 weeks in animals that developed hypertension in adult life as a result of having received an o-3-deficient diet during the prenatal period. This model of hypertension, developed by Weisinger et al, formed the basis of many studies by the same group.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In light of this evidence, it is interesting that Begg et al 22 reported in this issue that the expression of angiotensin-II 1A receptors and dopamine D3 receptors was significantly increased in the hypothalamic tissue of o-3-deficient animals at age 10 weeks, and the a2a and b1 adrenergic receptor expression was significantly reduced at 36 weeks in animals that developed hypertension in adult life as a result of having received an o-3-deficient diet during the prenatal period. This model of hypertension, developed by Weisinger et al, formed the basis of many studies by the same group.…”
mentioning
confidence: 99%
“…Begg et al 22 noted that at 10 weeks, the expression of angiotensin-II 1A receptors and dopamine D3 receptors significantly increased in the hypothalamic tissue, whereas at 36 weeks the a2a and b1 adrenergic receptor expression was significantly reduced in the o-3 DEF group. These alterations in the expression of angiotensin-II 1A , dopamine D3, a2a and b1 adrenergic receptors suggest that they may have a role in the pathobiology of hypertension, or they may simply be bystander changes.…”
mentioning
confidence: 99%
See 3 more Smart Citations